Digesti Monasit Bangka dengan Asam Sulfat - Prassanti, Riesna (EKSPLORIUM, 2012)
Technology of Bangka monazite processing with alkaline method has been mastered by PPGN BATAN with the product in the form of RE (Rare Earth) which is contain U < 2 ppm and Th 12 – 16 ppm. Hence, as comparator, the research of Bangka monazite processing with acid method using sulfuric acid has been done. The aim of this research is to obtain the optimal condition of Bangka monazite’s digestion using sulfuric acid so that all elements contained in the monazite that are U, Th, RE, PO4 dissolved as much as possible. The research parameter’s are monazite particle’s size, sulfuric acid consumption (weight ratio of monazite ore : sulfuric acid), digestion temperature, digestion time and consumption of wash water. The results showed that the optimal conditions of digestion are -250+325 mesh of monazite particle’s size, 1 : 2.5 of weight ratio of monazite ore : sulfuric acid, 190°C of digestion temperature, 3 hours of digestion time and 8 times of weight monazite’s feed of wash water with the recovery of digested U = 99.90 %, Th = 99.44 %, RE = 98.64 % dan PO4 = 99.88 %.